The problem of skipped generation and subclinical disease in familial breast‐ovarian cancer - Anne Dørum; Vera M. Abeler; Ketil Heimdal; Claes Tropé; Pål Møller (Acta Obstetricia et Gynecologica Scandinavica, 1997)
Background. The major gene for inherited breast ovarian cancer families shows high penetrance in female carriers. Daughters of living unaffected women in these families are supposed to have a low risk of cancer. Linkage analyses may be used to determine the probability that such families are linked to BRCA1 and, subsequently, to identify mutation carriers in such families. Linkage analyses are dependent upon correct diagnoses of all family members. Methods. We report one breast‐ovarian cancer family, prospectively observed, in which a mother and her daughter contracted ovarian and breast cancer almost simultaneously. Linkage analyses indicated that they both had the same BRCA1 mutation. The mother's sister had a possible premalignant lesion at oophorectomy. Discussion. We discuss the problems raised by the pathological classification of possible premalignant lesions, that linkage analyses are sensitive to misclassification of diagnoses, and probability for skipped generation.